The effect of co-induction of fentanyl compared to oxycodone on anesthetic depth and hemodynamic status in surgical patients under general anesthesia at Prof. Ngoerah Denpasar General Hospital - Tanggono, Aninda (Journal of Indonesia Vascular Access, 2025)
Introduction: Laryngoscopy and endotracheal intubation during general anesthesia can elicit sympathetic responses, including elevated blood pressure and heart rate. Fentanyl and oxycodone are opioids used for anesthesia co-induction to attenuate this response. This study aims to compare the co-induction effects of fentanyl and oxycodone on anesthesia depth and hemodynamic stability. Methods: This was a prospective observational study involving 40 adult patients with ASA I–II status undergoing general anesthesia at RSUP Prof. Ngoerah Denpasar. Subjects were randomized into two groups: fentanyl 2 µg/kg BW and oxycodone 0.2 mg/kg BW. All patients underwent standard induction protocols. The depth of anesthesia was assessed using the CONOX monitor (qCON), while hemodynamic status was evaluated through blood pressure, heart rate, and stroke volume via USCOM. Data were analyzed using t-tests and Mann-Whitney U tests with significance set at p<0.05. Results: There were no statistically significant differences in mean arterial pressure or heart rate between the groups (p>0.05), indicating similar hemodynamic responses. However, stroke volume reduction after intubation was significantly less in the oxycodone group (median ΔSV 3 vs 11.5; p<0.001). Additionally, qCON values showed better anesthesia depth with oxycodone (51.0 ± 5.8 vs 60.5 ± 7.5; p<0.001). Conclusion: Oxycodone co-induction results in better anesthesia depth and equal or superior hemodynamic stability compared to fentanyl. Oxycodone may be considered an effective alternative for co-induction in general anesthesia.